Question
Asked Oct 26, 2019
16 views

Solve the system by substitution 

-3x+4y= -1

4x+8y= -12

check_circle

Expert Answer

Step 1

We have equations :-3x+4y= -1, 4x+8y= -12.

Let us isolate equation (2) for x first.

Dividing equation (2) by 4 .

Then subtracting 2y on both sides.

-3x 4y 1
4x 8y 12
..equation(1)
..equation(2)
4x 8y
-12
4
x2y -3
x2y-2y-3-2y
x-3-2y
1n
help_outline

Image Transcriptionclose

-3x 4y 1 4x 8y 12 ..equation(1) ..equation(2) 4x 8y -12 4 x2y -3 x2y-2y-3-2y x-3-2y 1n

fullscreen
Step 2

Substituting x=-3-2y in first equation -3x+4y=-1 and solve for y.

We got y=-1.

-3r4y 1
-3(-3-2y) +4y -1
9 6y 4y -1
9 10y-1
Subtracting 9 on both sides
9-9 10y= -1-9
10y 10
Dividing both sides by 10
10y
-10
10
10
y =1
help_outline

Image Transcriptionclose

-3r4y 1 -3(-3-2y) +4y -1 9 6y 4y -1 9 10y-1 Subtracting 9 on both sides 9-9 10y= -1-9 10y 10 Dividing both sides by 10 10y -10 10 10 y =1

fullscreen
Step 3

Plugging y=-1 in x=-3-2...

x -3 2y
x-3-2(-1)
x-32
x-1
help_outline

Image Transcriptionclose

x -3 2y x-3-2(-1) x-32 x-1

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra